Public concerns about solar geoengineering research in the United States - Holly Jean Buck; Prerna Shah; Janet Z. Yang; Laura Arpan (Communications Earth & Environment)
Abstract Solar geoengineering is receiving increased private research funding at a time of growing social media speculation about government weather control. This can complicate public deliberation on solar geoengineering research. Using interviews (N = 64), focus groups (N = 10), and a national survey (N = 3076), we explore initial impressions of the US public on solar geoengineering research, including views on research and beliefs that atmospheric modification to combat global warming is currently ongoing. We find more opposition than support for research and a strong preference for research based in universities. Twenty percent of respondents believed it is partly or completely true that the US government is currently putting chemicals into the atmosphere to counteract global warming, and nearly half of respondents are unsure. We theorize belief in ongoing solar geoengineering not primarily as misinformation, but as para-environmentalism, representing a permutation of environmental concern that deserves further research and engagement.